PENGARUH WORK LIFE BALANCE, PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP KETERLEKATAN KERJA MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA ANGGOTA INSTANSI X - Ana Aristiyani; Muhammad Chairul Iman Nurdin; Monica Megita Veronica Assa; Lucia Rini Sugiarti; Fendy Suhariadi (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This study aims to determine the effect of work life balance, perceived organizational support on work engagement through job satisfaction as an intervening variable for members of Agency X. Respondents used were 45 members of Agency X. Research data was collected using a questionnaire. Data analysis was performed using Multiple Regression Analysis Techniques, t-test, path analysis, and sobel-test. Based on the research results it is known that (1) there is a positive effect of work life balance on job satisfaction (tcount = 2.703, probability (ρ) = 0.010). (2) There is a positive effect of perceived organizational support on job satisfaction (tcount = 3.435, probability (ρ) = 0.001). (3) There is a positive effect of work life balance on work attachment (tcount = 5.212, probability (ρ) = 0.000). (4) There is a positive effect of perceived organizational support on work engagement (tcount = 2.367, probability (ρ) = 0.023). (5) There is a positive effect of job satisfaction on work engagement (tcount = 4.129, probability (ρ) = 0.000).